Developing Speaking Instructional Materials through Contextual Teaching and Learning - Ina Daril Hanna; Rini Listyowati; Rabi’ah Rabi’ah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to produce speaking materials based on the students’ need and interests of Contextual Teaching Learning Approach. This research uses Research and Development design. In the context of the study, the researcher used questionnaire and interview guide. The draft of developed material focused on speaking and it was developed based on curriculum 2013. There are 11 units in this developed material.The researcher found that the materials was appropriate to the students. The students were interested to the topics so they were anthusiastic to speak in the class. It was because they thought that they really knew about the topic and it made them easy to prticipate the lesson. The students also interested with some pictures that display their classmate . It encourage them to read the materials anthusiasly.